Determine an effective golf swing by swing speed and impact precision tests - Wang, J.-J.; Yang, P.-F.; Ho, W.-H.; Shiang, T.-Y. (Journal of Sport and Health Science, 2015)
Background: To understand an effective golf swing, both swing speed and impact precision must be thoroughly and simultaneously examined. The aim of this study was to perform both swing speed test and impact precision test to ascertain what swing type determines an effective impact. Methods: Seven golfers from a college team (handicap: 0-12) were recruited to complete a swing speed test and impact precision test using a 5-iron club. A force plate and electromyography (EMG) system were used to collect data in the swing speed test to compare the difference between two motion sequences. High speed video cameras were used to determine the displacement of rotation center for impact precision test. Results: The results showed a significant difference (p < 0.01) in clubhead speed with different motion sequences and muscle contraction patterns. In the impact precision test, the displacement of the rotation center which defined as the inner center point of the C7 was significantly different (p < 0.05) between different ball impacted marks on club face. Conclusion: The vertical peak ground reaction force on left foot occurring before impact and the left latissimus dorsi contracting prior to the right pectoralis major represent a superior skill by allowing the club to strike the ball with normal collision at a faster speed.